2014
DOI: 10.4049/jimmunol.1302145
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ–Producing and IL-17–Producing γδ T Cells Differentiate at Distinct Developmental Stages in Murine Fetal Thymus

Abstract: γδ T cells develop at the double-negative (DN) 2 and DN3 stages and acquire functions to produce IL-17 and IFN-γ in fetal thymus. However, the relationship between differentiation stages and their functions was unclear. In this study, we found that, although IFN-γ–producing and IL-17–producing γδ T cells developed from DN2 cells, only IFN-γ–producing γδ T cells developed from DN3 cells, indicating the direct generation of IL-17–producing γδ T cells from the DN2 stage, not through the DN3 stage. Single-cell ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 50 publications
1
74
0
Order By: Relevance
“…Lck-GFP mice showed that the Lck protein was expressed in late DN2 (also known as DN2b) cells but not early DN2 (also known as DN2a) cells (41,42). We recently found that gd T cells were generated directly from both DN2a and DN2b stages (14). These results suggested that Cre recombinase driven by proximal Lck promoter might not delete RBP-Jk in DN2a-derived gd T cells, whereas Cre recombinase driven by the Rag-1 promoter almost completely inactivated RBP-Jk in gd expression on gdTCR + thymocytes was analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lck-GFP mice showed that the Lck protein was expressed in late DN2 (also known as DN2b) cells but not early DN2 (also known as DN2a) cells (41,42). We recently found that gd T cells were generated directly from both DN2a and DN2b stages (14). These results suggested that Cre recombinase driven by proximal Lck promoter might not delete RBP-Jk in DN2a-derived gd T cells, whereas Cre recombinase driven by the Rag-1 promoter almost completely inactivated RBP-Jk in gd expression on gdTCR + thymocytes was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…They are disproportionately distributed and persist in mucosal epithelia, such as skin, intestine, uterus, and lung, as tissue-associated, long-lived self-renewing cells that are important players in mucosal immunity in infections, wound healing, autoimmune disorders, and tumors (7)(8)(9)(10)(11). Interaction between Notch1 and Dll4 is essential for gd T cell development from T cell precursors, and Notch1 expression is maintained on gd T cells (12)(13)(14). We reported previously that the Notch1-Hes1 pathway is involved in the development of IL-17 + gd T cells in the fetal thymus (15).…”
mentioning
confidence: 99%
“…It remains to be established whether NK receptors as well as other innate receptors are expressed on in vivo on Bcl11b −/− DN3 thymocytes, similar to what was observed on ex vivo generated Bcl11b −/− DN3 thymocytes(16), which may interfere with appropriate signaling required for selection. Though γδT cells were reported to develop in normal numbers in the absence of Bcl11b(26, 27), more recent studies demonstrated that IL-17-producing γδT cells were absent in these mice(29). …”
Section: Bcl11b Is Essential For Multiple Checkpoints During T Celmentioning
confidence: 99%
“…Bcl11b was also identified as a radiation-induced tumor suppressor gene 1 (Rit1) in p53 + thymic lymphomas(24). Years of in depth study revealed that Bcl11b is necessary for several developmental checkpoints, including T cell commitment at DN2 stage(16, 25, 26), survival of DN3 and DP thymocytes(18, 27), β selection at DN3 stage, positive selection of CD4 and CD8 single positive (SP) thymocytes(18, 27, 28), development of Treg(22) and iNKT(23) cells, and most recently development of a subpopulation of γδ T cells(29). In mature T cells Bcl11b was demonstrated to control expansion and effector function of cytotoxic T cells (CTLs)(19), to restrict plasticity of Th17 cells by blocking expression of the Th2 program(21), as well as to control generation of iTreg cells from conventional CD4 + T cells, and overall to control the suppression function of Treg cells(22).…”
Section: Introductionmentioning
confidence: 99%
“…If γδ vs. αβ lineage choice were only determined stochastically, by the luck of rearrangement, then lineage fate should only be settled at the DN3a stage. However, both genetic and single-cell tests of differentiation in vitro show that by the time cells reach the DN3a stage, ready to carry out the definitive V-DJ rearrangements of their TCRβ genes, their ability to give rise to γδ cells has contracted to a small fraction of what it was earlier (Ciofani et al , 2006; Feng et al , 2011; Shibata et al , 2014). This implies that many cells with γδ potential leave the mainstream after the early DN2 stages, even before the peak of TCR gene rearrangement activity.…”
Section: Introduction: T-cell Identity and Processing Of T-cell Prmentioning
confidence: 99%